Janchelevici : dessins - Toussaint van Boelaere, F.V. (Anvers : De Magneet, 1946)
Bibliotheek Camille Huysmans
Nr. 366 van 475 luxe-exemplaren, genummerd van 26 tot 500
Frans
Album
Keywords: tekenkunst